Efektifitas Pikukuh Baduy Tentang Perkawinan Kebal Cerai Bagi Masyarakat Adat Baduy - Anwar, Jarkasi; Muslih, Muhamad (MADINAH, 2021)
The Baduy indigenous people as one of the ethnic groups in Indonesia have various unique and diverse cultural characteristics. The ethnic groups in Banten do not recognize divorce. Baduy people are only allowed to marry once in their lifetime unless their spouse (wife or husband) dies, then they are allowed to remarry. Apart from divorce, in Baduy society there is also a prohibition on polygamy and polyandry because Baduy people are only allowed to marry one person. Men in Baduy customs are indeed forbidden to practice polygamy because Baduy society is very thick with past culture. This is one proof that the Sunda Wiwitan religion is still highly adhered to and obeyed. The house on stilts with one door has a deep meaning. One door symbolizes loyalty so they can only have one wife. Divorce is something that is forbidden by their custom. If a divorce occurs, they are punished with very severe sanctions for them, one of which is expulsion from the Baduy area. The Baduy customary law which does not allow the community to divorce is known as the Divorced Immune Marriage. This study describes the Pikukuh Baduy (rules of prohibition from ancestors) regarding Divorced Marriage in Baduy and applies to all Baduy indigenous peoples, both Inner Baduy and Outer Baduy. The long-term goal to be achieved from this research is to find out the causes and reasons for this divorce-immune marriage and how to comply with it because according to some sources there are still those who violate this Baduy customary pikukuh. The consequences of this violation of the Baduy customary pikukuh will also be analyzed systematically and then look for positive solutions. The specific target to be achieved from this research is to strive for the Baduy community to continue to follow ancestral customs for the sake of creating the sustainability of the life of the Baduy indigenous people. Life in Baduy is very simple, but they can live in peace, serenity, and rarely get into conflict because they can adhere to the traditional rules of their ancestors. This can be a mirror for other communities in Indonesia. This will also have a positive impact on preserving the culture of the Unitary Republic of Indonesia, which is diverse in culture with its motto Bhinneka Tunggal Ika. This research uses normative juridical and sociological normative legal research methods. This research is descriptive analytical and uses Primary Data Sources and Secondary Data Sources. Descriptive in this research in the form of a description of the situation, conditions, circumstances, and the reality of the customary pikukuh that exist in the Baduy Tribe community. Then analyze what the problem is in order to find a solution to the problem. The source of the data used in this study was obtained from Library Research. Normative Jurisdiction in this study is a discussion of several existing regulations. Sociological Normative Research on law constructs law as a system of laws and regulations that have existed so far and then constructed in a society's behavior. Sociological research on law observes how the law lives in the community and what is the characteristic of a community behavior in an area in an aspect of social life to be further described, compiled, and analyzed descriptively to get a complete picture of the relationship between interests. and all values ​​that are embraced and believed by the community in the area, namely in Baduy.